Cost-effectiveness analysis of ambroxol for the treatment of Chinese patients with Gaucher disease - Huang, Yueyang; Yuan, Hongmei; Huang, Zhe (Frontiers in Medicine, 2025)
BackgroundGaucher disease (GD) is an autosomal recessive disorder with a wide range of clinical symptoms that cause abnormal function of parenchymal organs such as liver and spleen in patients. Enzyme replacement therapy, represented by imiglucerase, is a common approach for GD treatment. However, limited efficacy and high cost are important factors restricting its use. Ambroxol has gradually attracted attention due to its ease of administration, safety, and efficacy. However, there is no pharmacoeconomic evaluation of ambroxol for the treatment of GD in China. The cost-effectiveness profile of ambroxol combined with imiglucerase therapy for the treatment of GD, as opposed to imiglucerase monotherapy, needs to be investigated.ObjectiveThis study aimed to analyze the cost-effectiveness of ambroxol for GD in China from the perspective of the Chinese healthcare system.MethodsWe constructed an eight-state Markov model based on the disease characteristics of GD. The Markov cycle was 1 month. The time horizon was 6 years. The willingness-to-pay threshold was chosen to be 1–3 times the gross national product (GDP) per capita. The incremental cost-effectiveness ratio (ICER) was calculated from the base-case analysis, and one-way sensitivity analyses and probabilistic sensitivity analyses were performed.ResultsThe ICER value was ¥223,726.70, which was between 1 and 3 times GDP per capita. Sensitivity analysis showed that the cost of imiglucerase had a significant effect on ICER as well as demonstrating the stability of the results.ConclusionAmbroxol combination therapy is a cost-effective regimen compared with imiglucerase monotherapy.